Evaluation of a preoperative team briefing: a new communication routine results in improved clinical practice. Issue 6 (8th February 2011) - Lingard, Lorelei; Regehr, Glenn; Cartmill, Carrie; Orser, Beverley; Espin, Sherry; Bohnen, John; Reznick, Richard; Baker, Ross; Rotstein, Lorne; Doran, Diane
Abstract : Background: Suboptimal communication within healthcare teams can lead to adverse patient outcomes. Team briefings were previously associated with improved communication patterns, and we assessed the impact of briefings on clinical practice. To quantify the impact of the preoperative team briefing on direct patient care, we studied the timing of preoperative antibiotic administration as compared to accepted treatment guidelines. Study design: A retrospective pre-intervention/post-intervention study design assessed the impact of a checklist-guided preoperative team briefing on prophylactic antibiotic administration timing in surgical cases (N=340 pre-intervention and N=340 post-intervention) across three institutions. χ 2 Analyses were performed to determine whether there was a significant difference in timely antibiotic administration between the study phases. Results: The process of collecting and analysing these data proved to be more complicated than expected due to great variability in documentation practices, both between study sites and between individual practitioners. In cases where the timing of antibiotics administration was documented unambiguously in the chart (n=259 pre-intervention and n=283 post-intervention), antibiotic prophylaxis was on time for 77.6% of cases in the pre-intervention phase of the study, and for 87.6% of cases in the post-intervention phase (p<0.01). Conclusions: Use of a preoperative team checklist briefing was associated with improved physician compliance with antibiotic administration guidelines. Based on the results, recommendations to enhance timely antibiotic therapy are provided.